Blood Drops Red Words: Considering VestAndPage’s blood writing in performance (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This self-reflective article addresses how VestAndPage (Verena Stenke & Andrea Pagnes) have been exploring blood in a bifold symbolic value as a performative tool since 2006: connection–separation, immutability–violation, abjection–access. After medical complications and becoming blood donors, the artist duo has started deploying surgical instruments in their performances to engrave Pagnes’s skin, extract his blood, and ritualise this process into stream-of-consciousness writing. Thus, blood becomes a device of intimacy that allows them to transcend the representation of concepts and explore the human condition’s transitory presence and fragile nature.
Keywords: performance art; blood; intimacy; momentary poetry